Aechmea distichantha - Edward F. Gilman (EDIS)
The attractive green foliage of this easy-care, durable bromeliad is a perfect background for the brilliant, springtime flower stalk that emerges from the tight center rosette of leaves (Figure 1). The flower stalk is composed of a cluster of red, showy bracts lasting several months. It is the long-lasting bracts that are most noticeable and stand about 2 feet off the ground. They are very striking in full bloom. This document is Fact Sheet FPS-15, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: October, 1999. Reviewed October 2003.